Buku Fotografi Tari Lengger Lanang: Media Pembelajaran Berbasis Visual untuk Pendidikan Seni dan Budaya - Galen, Bintang Abdad; Rismantojo, Sandy; Aryani, Dewi Isma (Cetta: Jurnal Ilmu Pendidikan, 2025)
Lengger Lanang is a traditional Banyumas dance art whose existence is threatened by changes in public perception. This art, which originally functioned as a ritual for Dewi Sri and even a war tactic during the Diponegoro era, has experienced a shift in values ​​due to the stigma against cross-gender culture. This study aims to design educational media to preserve Lengger Lanang by providing an in-depth perspective on the history and lives of its dancers. The study uses a descriptive qualitative approach with creative methods. Data collection was carried out through literature studies, observations, and in-depth interviews with Lengger Lanang dancers. Data were analyzed thematically to identify key narratives. The results show that the philosophical values ​​of Lengger Lanang are far deeper than just a cross-gender performance. Three main narratives were identified: (1) spirituality and its relationship to agriculture, (2) heroism and cultural strategies in fighting colonialism, and (3) the struggle for identity and dedication of Lengger Lanang dancers who maintain tradition. These narratives were then realized in the design of a photographic novel book that combines strong visuals with narrative text. The photographic novel book has proven effective as a strategic medium for educating the public. This media successfully shifted the focus from gender stigma to an appreciation of the historical, artistic, and human interest values ​​behind the Lengger Lanang mask. The study's conclusions recommend the use of a narrative-based creative design approach to preserve other intangible cultural heritage.